2017
DOI: 10.31603/pharmacy.v3i2.1744
|View full text |Cite
|
Sign up to set email alerts
|

KAJIAN DRUG RELATED PROBLEMs PENGGUNAAN ANTIBIOTIK PADA PASIEN PEDIATRIK DI RSUD KOTA SEMARANG

Abstract: Drug Related Problems (DRPs) merupakan masalah yang berhubungan dengan obat yang banyak terjadi di pelayanan kesehatan. Tujuan penelitian ini untuk mengetahui profil kejadian DRPs, profil antibiotik yang mengalami DRPs, dan hubungan antara Drug Related Problems penggunaan antibiotik dengan luaran terapi. Penelitian ini merupakan penelitian observasional analitik dengan rancangan retrospective cohort study. Subyek penelitian yang memenuhi kriteria inklusi sebanyak 128 pasien, dimana terdapat 78 kejadian drug re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Birarra et al 13 reported that the incidence of drug interaction in pediatric ward of Zewditu Memorial Referral Hospital, Addis Ababa, Ethiopia is 38.6%. Whereas a study in District General Hospital in Semarang, Central Java, it was reported as much as 42.32% 18 and another study conducted in District General Hospital and Muhammadiyah Private Hospital in Yogyakarta was 56.4%. 3…”
Section: Drug Interactionsmentioning
confidence: 85%
See 3 more Smart Citations
“…Birarra et al 13 reported that the incidence of drug interaction in pediatric ward of Zewditu Memorial Referral Hospital, Addis Ababa, Ethiopia is 38.6%. Whereas a study in District General Hospital in Semarang, Central Java, it was reported as much as 42.32% 18 and another study conducted in District General Hospital and Muhammadiyah Private Hospital in Yogyakarta was 56.4%. 3…”
Section: Drug Interactionsmentioning
confidence: 85%
“…Abrogoua et al 20 reported that the noncompliance at a pediatric unit in Cote d'Ivoire is 24.1%. Whereas, studies conducted by Arfania et al 3 and Timur et al 18 found that non-compliance of antibiotic use among pediatric patients are 1.28 and 9.88%, respectively.…”
Section: Therapy Without Indicationmentioning
confidence: 92%
See 2 more Smart Citations